FIRST RECORD OF BLACK AND WHITE EAGLE Spizaetus Melanoleucus IN THE ALLPAHUAYO MISHANA NATIONAL RESERVE, AT NORTHEASTERN OF THE PERUVIAN AMAZON - TORRES VÁSQUEZ, Maria Isabel (2017)
We report the presence of the Black-and-white Hawk-Eagle Spizaetus melanoleucus in the Allpahuayo Mishana National Reserve (AMNR) and at the same time we extend its range to the north of the Amazon river, increasing in the AMNR the richness of species to 498. We describe some details about the behavior of the species and the current state of conservation of the forests where the individuals were sighted.